Sistem Informasi Data Bahan-Bahan Material Pada UD. Sinar Baru Sigambal Berbasis Web - Siregar, Febri Syahrial (Universitas Labuhanbatu, 2022)
Writing this final project aims to assist in how to design an application program in realizing and creating a program that will be run. The information system needed by UD. Sinar Baru which provides convenience in the activities of promoting materials needed by the community quickly, accurately and integrated. The methodology used is UML (Unified Modeling Language). With the language used is PHP and the database used by MySQL, Information System Design Data Material Materials UD. Sinar Baru Sigambal produces information systems for data management of materials that can facilitate the sales process. Material is raw material that has not been processed, but sometimes it has been processed before being used for further production processes. Material is consumer material that has not been completed. Material is also needed by people who want to build a building.